Dinamika Institusi Pendidikan Seni: Antara Pendidikan Formal Dan Perkembangan Praktis Berkesenian Di Indonesia - Rusmana, Tatang; Yuniarni, Yuniarni (Institut Seni Indonesia Padangpanjang, 2023)
Science and art provide humanity on complementary paths. Both contain creative thinking and problem solving. Science seeks answers to questions about the external, physical world; the answer to this forms the basis of our present technological progress. While art depicts the development of our inner world namely; intuitive, emotional, spiritual and creative aspects of human beings. The real world is explained through science and revealed through works of art. Humans need both science and art if they balance function with the meaning of life. Art is an activity that occurs by the process of